1990
DOI: 10.2307/3430971
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Studies in Human Populations Exposed to Gas Leak at Bhopal, India

Abstract: Frequencies of chromosomal abnormalities, sister chromatid exchanges, and replicative index were assessed following peripheral lymphocyte culture in 129 individuals from Bhopal, India. Ofthese, 83 persons (40 male and 43 female) had been exposed directly to the methyl isocyanate (MIC) gas after the accident at the Union Carbide plant on December 2 and 3,1984. The remaining 46 samples were taken from age-matched unexposed persons in the same city. Chromosome aberrations were recorded at first cycle metaphase (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Developing methods for studying genome-wide effects of occupational or inadvertent exposure to environmental contaminants, which affect human health, and elucidating the molecular mechanisms of these effects are now major concerns. Isocyanates, including MIC have wide industrial applications, although they are mutagenic, alter the genome (Mason et al, 1987;Anderson et al, 1988;Kar et al, 1989) and can produce varied chromosomal abnormalities in individuals exposed to them (Goswami et al, 1990;Ghosh et al, 1990). There are reports that defects in the cellular response to DSBs can lead to genetic alterations, chromosomal instability, and ultimately malignant transformation (Mills et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing methods for studying genome-wide effects of occupational or inadvertent exposure to environmental contaminants, which affect human health, and elucidating the molecular mechanisms of these effects are now major concerns. Isocyanates, including MIC have wide industrial applications, although they are mutagenic, alter the genome (Mason et al, 1987;Anderson et al, 1988;Kar et al, 1989) and can produce varied chromosomal abnormalities in individuals exposed to them (Goswami et al, 1990;Ghosh et al, 1990). There are reports that defects in the cellular response to DSBs can lead to genetic alterations, chromosomal instability, and ultimately malignant transformation (Mills et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It may induce DNA damage, apoptosis, over‐expression of cytokines and genomic instability (Kundu and Surh, 2008). Therefore down regulation of components of the DNA damage response mechanisms could enhance genomic instability and facilitate the proliferation of pre‐cancerous cells (Gorgoulis et al., 2005). As MIC can initiate DNA damage, apoptosis, oxidative stress and inflammation in cultured human lymphocytes (Mishra et al., 2008), it is very likely that it is linked to genomic instability.…”
Section: Introductionmentioning
confidence: 99%
“…In a study involving 43 gas-exposed women and 40 gas-exposed men 3 years after the disaster, a significant increase in chromosomal aberration was reported; these aberrations included breaks, gaps, and dicentric rings, which were more marked in females than in males (Ghosh et al, 1990). Chromosomal aberrations (Goswami, 1986;Ghosh et al, 1990) and cell cycle abnormalities have been identified in Bhopal victims (Deo et al, 1987).…”
Section: Genotoxicitymentioning
confidence: 95%
“…Chromosomal aberrations (Goswami, 1986;Ghosh et al, 1990) and cell cycle abnormalities have been identified in Bhopal victims (Deo et al, 1987).…”
Section: Genotoxicitymentioning
confidence: 98%
“…after the accident on a sample of 40 exposed males and 40 exposed females revealed a statistically higher frequency of chromosomal aberrations among those exposed compared with non-exposed controls. 3 These chromosomal aberrations were more pronounced in females.…”
Section: Introductionmentioning
confidence: 94%